Traditional herbal medicines: potential degradation of sterols and sterolins by microbial contaminants - D. du Plessis-Stoman; T. Downing; M. van de Venter; S. Govender (South African Journal of Science)
Medicinal plants with a high content of sterols and sterolins, such as Bulbine natalensis (rooiwortel) and Hypoxis hemerocallidea (African potato), are commonly and inappropriately used in South Africa for the treatment of HIV/AIDS due to the inaccessibility of antiretroviral drugs. This study investigated the presence of active compounds, such as sterols and sterolins, in the herbal medicines. The research was carried out in the Nelson Mandela Metropole area. The effect of microbial contaminants isolated from the medicines on sterols and sterolins of rooiwortel extracts was assessed. Sterols and sterolins were detected in rooiwortel, raw African potatoes and one ready-made mixture. Co-incubation of rooiwortel with bacteria (Bacillus spp. and Pseudomonas putida) and fungi (Aspergillus spp., Penicillium spp. and Mucor spp.) that were isolated from these samples increased the rate of degradation of sterols and sterolins over time, with slower degradation at 4Â°C than at 28Â°C.